Scheduling N Jobs on Identical Parallel Machines in PT XYZ to Reduce Total Tardiness Using Earliest Due Date Rules and Job Splitting Property - Giovanny, Tengku Khalida Zia; Damayanti, Dida Diah; Oktafiani, Ayudita (eProceedings of Engineering, 2023)
Abstract-This research focus on reducing total tardiness on single-stage identical parallel machine in PT XYZ. The method used are EDD rules where the job is sorted based on earliest due date and job splitting property where the job is split between the machine with maximum tardiness and the machine with minimum tardiness. The proposed method managed to yield successful result by decreasing the total tardiness up to 33%. Keywords- identical parallel machine scheduling, EDD, job splitting property